Association between dog ownership and type 2 diabetes in later life: the Helsinki birth cohort study. Issue 1 (1st January 2019) - Laine, Merja K.; Wasenius, Niko S.; Lohi, Hannes; Simonen, Mika; Tiira, Katriina; Eriksson, Johan G.; Salonen, Minna K.
ABSTRACT: Dog ownership has been reported to have beneficial effects on physical activity and emotional well-being, both known to reduce the risk for type 2 diabetes (T2D). The aim of this study was to evaluate the association between dog ownership during the whole life course and having T2D in later life. The study subjects consisted of 731 people (307 men and 424 women) from the Helsinki Birth Cohort Study. We assessed dog ownership with questionnaires, for every decade of life as well as current dog ownership. We investigated the associations between dog ownership and T2D with generalised estimating equation models and with generalised linear models. At a mean age of 71.0 (standard deviation [SD] 2.6) years, 13% of the participants had T2D. Dog ownership prior to the clinical examination was not associated with T2D (p ≥ 0.51). In men, but not in women, current dog owners had greater odds of having T2D compared with the non-owners when adjusted for age when clinically examined, socio-economic status, smoking, leisure-time physical activity, chronic diseases (OR = 3.32, 95% confidence interval 1.25–8.79, p = 0.016). In the age group of people around 70 years, dog ownership is not associated with reduced odds for developing T2D. Abbreviations: BMI: body mass index; CI: confidence interval; GEE: generalised estimating equation; HBCS: Helsinki Birth Cohort Study; KIHD: Kuopio Ischemic Heart Disease; LTPA: leisure-time physical activity; MET: metabolic equivalent of task; OGTT: oral glucose tolerance test; OR: Odds ratio; SD: standard deviation; SES: socio-economic status; T2D: type 2 diabetes